Development and validation of a disease model for postmenopausal osteoporosis. - Gauthier, A; Kanis, J; Martin, M; Compston, J; Borgström, F; Cooper, C; McCloskey, E; Committee of Scientific Advisors, International Osteoporosis Foundation (2011)
This article describes the development of a model for postmenopausal osteoporosis (PMO) based on Swedish data that is easily adaptable to other countries.